How B2B relationships influence new product development in entrepreneurial firms? The role of psychological tension - Zheng, Leven L; Zhang, Yameng; Zhan, Wu; Sharma, Piyush (Elsevier, 2021)
Although tension commonly exists in business-to-business (B2B) relationships, past research pays little attention to the potential dark side effects of psychological tensions, especially those between entrepreneurial firms and their client firms, despite their significant impact on these firms’ performance. We address this important research gap by exploring the nature and impact of psychological tensions between entrepreneurial firms and their client firms during the conceptualization and commercialization stages of the new product development (NPD) process. We employ a qualitative approach to conduct semi-structured interviews with 19 entrepreneurial firms operating in the artificial intelligence field in China, and identify two types of psychological tensions at the conceptualization stage (fear of losing the B2B relationship and divergent expectations) and one type of psychological tension at the commercialization stage (attention embeddedness). We also find that fear of losing the B2B relationship and divergent expectations lead to technological decontextualization, while attention embeddedness yields singular learning.